Physical demands and physiological response of soccer referees in high-level matches: A systematic review - Lingling Zhang; Soh Kim Geok; Mohd Rozilee Wazir Norjali Wazir; Liang Qin (PLoS ONE, 2025)
Background The match physical demands placed on soccer referees are intrinsically connected to their capacity to make accurate judgments, becoming the second most studied theme in associate soccer refereeing. Objective This study aims to review the external and internal load performed by soccer referees in high-level competitions, to identify changes in these indicators over different periods as the competition progresses, and to analyze the standards for dividing speed zones and heart rate zones. Methods Web of Science, PubMed, Scopus, and EBSCOhost were thoroughly searched. Grey literature sources and Google Scholar were also consulted, with a focus on analysing and comparing the physical demands of soccer referees at different phases of high-level matches. Results A total of 14 manuscripts were included in this review. Studies revealed that the total distance (TD) covered by referees during a full match ranged from 9 to 12 km. High-intensity running (HIR) constituted 2.0–18.7% of TD, accounting for approximately 38% of total time (TT). Referees reached 80–100% of their maximal heart rate during matches. The standards for dividing speed zones and heart rate zones varied among the selected studies. Discussion This systematic review aimed to provide a comprehensive overview of referees’ physical demands (e.g., TD, HIR, and HR) to offer practitioners valuable biological data for training and competition preparation. The lack of uniform criteria for dividing speed and heart rate zones limits data collection, thereby affecting the reporting of distances covered at different exercise intensities.